2010
DOI: 10.1016/j.ijimpeng.2009.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of strain in fabrics under ballistic impact using embedded nichrome wires, part II: Results and analysis

Abstract: A new technique using nickel-chromium wire, called the NiCr (Nichrome R ) wire technique, has been presented in a rst paper describing the technique [1]. This second paper focuses on the results obtained when this new technique is applied to ballistic fabrics. Strain distributions on the layer impacted, as well as in dierent layers, are presented. An energy balance based on the strains is shown to provide reasonable values for the elastic energy stored by the yarns. Failure times of the rst layer as a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…. A similar explanation is provided by Chocron et al 37,38 based on their measured strains in the secondary yarns consistent with Cunniff's description. They measured strains in a multi-layer Kevlar fabric during ballistic impact by embedding Nickel-Chromium (NiCr) wires in the secondary yarns.…”
supporting
confidence: 83%
“…. A similar explanation is provided by Chocron et al 37,38 based on their measured strains in the secondary yarns consistent with Cunniff's description. They measured strains in a multi-layer Kevlar fabric during ballistic impact by embedding Nickel-Chromium (NiCr) wires in the secondary yarns.…”
supporting
confidence: 83%
“…The following describes how we combined the data from this study to calculate the possible maximum tensile dissipation of a multilayer panel. Chocron et al 17,18 has experimentally shown that the local strain in the yarn depends on the impact velocity while it is much less dependent on the layer number. They have also shown that the initiation of an elongational event at early time of impact occurs at a regular interval of time, which is the time needed for the compression wave created by the bullet to reach the adjacent layer.…”
Section: Resultsmentioning
confidence: 99%
“…On the experimental part, several investigations have been conducted to investigate lowvelocity and ballistic impact response of yarns, 1D, 2D and 3D fabrics [48,[72][73]. Figure 6 depicts different damage modes for various fiber architecture of composites.…”
Section: Fiber Architecturementioning
confidence: 99%